Machine Learning to Assess for Acute Myocardial Infarction Within 30 Minutes. Issue 2 (21st February 2022) - McCord, James; Gibbs, Joseph; Hudson, Michael; Moyer, Michele; Jacobsen, Gordon; Murtagh, Gillian; Nowak, Richard
Abstract : Variations in high-sensitivity cardiac troponin I by age and sex along with various sampling times can make the evaluation for acute myocardial infarction (AMI) challenging. Machine learning integrates these variables to allow a more accurate evaluation for possible AMI. The goal was to test the diagnostic and prognostic utility of a machine learning algorithm in the evaluation of possible AMI. We applied a machine learning algorithm (myocardial-ischemic-injury-index [MI 3 ]) that incorporates age, sex, and high-sensitivity cardiac troponin I levels at time 0 and 30 minutes in 529 patients evaluated for possible AMI in a single urban emergency department. MI 3 generates an index value from 0 to 100 reflecting the likelihood of AMI. Patients were followed at 30–45 days for major adverse cardiac events (MACEs). There were 42 (7.9%) patients that had an AMI. Patients were divided into 3 groups by the MI 3 score: low-risk (≤ 3.13), intermediate-risk (> 3.13–51.0), and high-risk (> 51.0). The sensitivity for AMI was 100% with a MI 3 value ≤ 3.13 and 353 (67%) ruled-out for AMI at 30 minutes. At 30–45 days, there were 2 (0.6%) MACEs (2 noncardiac deaths) in the low-risk group, in the intermediate-risk group 4 (3.0%) MACEs (3 AMIs, 1 cardiac death), and in the high-risk group 4 (9.1%) MACEs (4 AMIs, 2 cardiac deaths). The MI 3 algorithm had 100% sensitivity for AMI at 30 minutes and identified a low-risk cohort who may be considered for early discharge.